2020
DOI: 10.1109/ojcoms.2020.3010514
|View full text |Cite
|
Sign up to set email alerts
|

Low-Resolution Quantization in Phase Modulated Systems: Optimum Detectors and Error Rate Analysis

Abstract: This paper studies optimum detectors and error rate analysis for wireless systems with low-resolution quantizers in the presence of fading and noise. A universal lower bound on the average symbol error probability (SEP), correct for all M-ary modulation schemes, is obtained when the number of quantization bits is not enough to resolve M signal points. In the special case of M-ary phase shift keying (M-PSK), the maximum likelihood detector is derived. Utilizing the structure of the derived detector, a general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…We also assume that full channel state information (CSI) is available at the receiver. Similar to our previous work in [8], the motivation behind our model with full-precision CSI is two-fold. First, in [42], it was shown that it is possible to attain a high channel estimation precision with the use of low-resolution ADCs by increasing the number of training symbols in the closed-loop estimation process.…”
Section: B Receiver Architecturementioning
confidence: 96%
See 4 more Smart Citations
“…We also assume that full channel state information (CSI) is available at the receiver. Similar to our previous work in [8], the motivation behind our model with full-precision CSI is two-fold. First, in [42], it was shown that it is possible to attain a high channel estimation precision with the use of low-resolution ADCs by increasing the number of training symbols in the closed-loop estimation process.…”
Section: B Receiver Architecturementioning
confidence: 96%
“…By using DVO as our main performance metric, we determine communication reliability to first order. We propose three lowcomplexity antenna selection strategies for data detection and we obtain reliability regimes for the proposed strategies, analogous to those obtained in the case of SISO systems in [8]. We establish their asymptotic optimality properties as a function of the quantization bits in terms of DVO, and compare their performance with the one achieved by the derived maximum likelihood (ML) detector.…”
Section: Introduction a Background And Motivationmentioning
confidence: 95%
See 3 more Smart Citations